Performance evaluation on aquatic product cold-chain logistics - Wenbing Wu; Yanwei Deng; Mingyu Zhang; Yihua Zhang (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: The requirements for high quality and diversification aquatic products are increasing with the improvement of Chinese living standard. However, the distribution between the place of production and the place of consumption are uneven, which results in large cold-chain logistics demand for aquatic products. At present, the low-level development of cold chain logistics has a bad impact on the circulation of aquatic products in China. So it is very urgent to develop cold-chain logistics in China. Design/methodology/approach: In order to do this, we apply performance evaluation, a well-known management tool, to study Chinese aquatic product cold-chain logistics. In this paper we first propose SISP (Subjects, Indexes, Standards, and Phases of performance evaluation) model and ACSSN model (Aquatic product, Customer, Supply Chain, Society, and Node enterprises of supply chain) for aquatic products cold-chain logistics performance evaluation. Then an ANP-Fuzzy method is proposed to evaluate the operational performance of Shandong Oriental Ocean Sci-Tech Co., Ltd. Furthermore, a system dynamic model is built to simulate the impact of temperature on the profits in aquatic products cold-chain sales section. Findings: We find out within a reasonable temperature range, lower temperature brings higher profit level. Also, performance improvement methods are proposed and the simulation of performance evaluation system is developed. Practical implications: Our findings can help to improve the level of aquatic product coldchain logistics in China. Originality/value: The paper proposes the SISP (Subjects, Indexes, Standards, and Phases of performance evaluation) model and ACSSN model (Aquatic product, Customer, Supply Chain, Society, and Node enterprises of supply chain) for aquatic products cold-chain logistics performance evaluation.
Keywords: 650; aquatic products; cold-chain logistics; performance evaluation; performance improvement